Information System Development for Receiving and Handling Customer Complaints in Public Services - Komarudin, Komarudin (Devotion : Journal of Research and Community Service, 2023)
Good public service is one indicator of the success of a government in providing satisfaction for the community. Along with the development of information technology, the government is also trying to improve public services by developing information systems that make it easier for people to make complaints or complaints about public services. This research aims to develop an information system that can improve the receipt and handling of customer complaints on public services. The method used in this research is the waterfall method. Data will be collected through interviews with relevant parties in public services, direct observation of the existing complaint system, and literature study related to the development of information systems. The results of this research are expected to produce an effective and efficient information system in receiving and handling customer complaints in public services. In this case, the information system can facilitate customers in making complaints, as well as speeding up the handling process and responses from related parties. So that it is expected to increase customer satisfaction with the public services provided.